Challenges and Opportunities for the community of Food Sciences to contribute Towards a Society of Healthier Consumers and a Better World - Harris N. Lazarides (International Journal of Food Studies)
Despite the tremendous scientific and technological achievements in the production of food, human well-being has not been served to a satisfactory extent. Millions of people are literally killing themselves by excessive eating or wrong use of food, leading to obesity and nutrition-related diseases. At the same time millions of people continue to suffer from lack of food, leading to starvation, malnutrition and death, often before reaching adult age. Parallel to striving for better-safer-healthier food, the community of Food Sciences is faced with the challenge to help educate the average consumer on how to select, handle, store and use food for safe and healthy eating. The need to reshape and reform public education to better serve this task is obvious. What is also obvious is the need for medical professionals to recognize healthy eating (and exercise) as the most valuable tool in preventive medical care. This perspective will concentrate on challenges and opportunities for Food Scientists/Engineers: to contribute towards a society of well-informed, self-protected, active and considerate citizens; to support public (food-related) education and actively participate in the fight against obesity and nutrition-related diseases; to intervene in decision making bodies and underline the importance of education on nutrition and food; to invent avenues and possibilities to contribute to the fight against world hunger; and all in all, to contribute towards a healthier world, a world that will not be split between hunger and obesity.